Synthesis, spectroscopic, thermal and anti-microbial studies of transition metal complexes of hydrazone derived from 4,6-diacetylresorcinol and S-methyldithiocarbazate - Emara, Adel Abbas Ahmed; Taha, Ali Mahmoud; Mashaly, Mahmood Mohamed; Adly, Omima Mohamed Ibrahim (European Journal of Chemistry, 2015)
New series of copper(II), nickel(II), cobalt(II), zinc(II), cadmium(II), iron(III) and oxovanadium(IV) complexes of hydrazone, H3L, ligand derived from the condensation of S-methyldithiocarbazate and 4,6-diacetylresorcinol, in the molar ratio 1:1, has been synthesized. All the metal complexes are dimmers. The structures of the ligand and its transition metal complexes were characterized by elemental analyses, spectral (Infrared, electronic, Mass, 1H NMR and ESR) data and magnetic susceptibility, molar conductivity measurements and thermal gravimetric analysis. The structure of the ligand is dibasic tridentate with ONS sites. The bonding sites, in all cases, are the azomethine nitrogen, phenolic oxygen and thiol sulfur atoms, as illustrated from the spectral data. The metal complexes exhibit different geometrical arrangements such as square planar, tetrahedral, square pyramidal and octahedral arrangements. Kinetic parameters (DG, DH, DS and DE) of the metal complexes were calculated from the thermal behaviour of the metal complexes using Coats-Redfern method. The ligand and its metal complexes were screened for its antimicrobial activity against Staphylococcus aureus and Staphylococcus pyogenes as Gram-positive bacteria, Pseudomonas phaseolicola and Pseudomonas fluorescens as Gram-negative bacteria and the fungi Fusarium oxysporum and Aspergillus fumigatus.